2006
DOI: 10.4049/jimmunol.176.11.6443
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Alveolar Macrophage Apoptosis Prolongs Survival of Rats and Mice withPneumocystisPneumonia

Abstract: The number of alveolar macrophages is decreased in patients or animals with Pneumocystis pneumonia (Pcp). This loss of alveolar macrophages is in part due to apoptosis caused by Pneumocystis infection. The mechanism of apoptosis induction is unknown. Cell-free bronchoalveolar lavage fluids from Pneumocystis-infected rats or mice have the ability to induce apoptosis in normal alveolar macrophages. To characterize the mechanisms by which apoptosis proceeds in alveolar macrophages during Pcp, specific caspase inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 57 publications
3
45
0
Order By: Relevance
“…Furthermore, their marked suppressive activities may in some situations exert beneficial effects during exuberant host inflammation, including activity in suppressing TNF-a and macrophage inflammatory protein-2 (36,37). Inflammatory responses by macrophages and epithelial cells also provide important functions in Pneumocystis host defense (67,68). However, caution must be exercised, because these agents may also suppress important DC/lymphocyte-based IL-23/IL-17 responses, which are required to clear fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, their marked suppressive activities may in some situations exert beneficial effects during exuberant host inflammation, including activity in suppressing TNF-a and macrophage inflammatory protein-2 (36,37). Inflammatory responses by macrophages and epithelial cells also provide important functions in Pneumocystis host defense (67,68). However, caution must be exercised, because these agents may also suppress important DC/lymphocyte-based IL-23/IL-17 responses, which are required to clear fungal infections.…”
Section: Discussionmentioning
confidence: 99%
“…Alveolar macrophages that undergo apoptosis in response to S. pneumoniae infection may contribute to enhanced bacterial killing, and additionally restrict the proinflammatory response to inhaled bacteria, thus attenuating overwhelming local and systemic proinflammatory responses to S. pneumoniae infection. At the same time, alveolar and exudate macrophages play important roles in the resolution/repair phase of the disease, thus serving to regain alveolar and lung homeostasis (22)(23)(24)(25)(26). The currently presented data, making use of a largely (yet not exclusively) DC-specific growth factor for the first time, aim at gaining further insights into the role of mononuclear phagocyte subsets other than classical alveolar macrophages in the lung host defense to S. pneumoniae infection and highlight the critical importance of a fine-tuned mononuclear phagocyte network within the lung for an optimal host defense to inhaled bacterial pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicated that apoptosis contributed to ϳ60% loss of alveolar macrophages during Pcp. This 60% loss of alveolar macrophages by apoptosis is physiologically significant because suppression of this apoptosis by administration of the caspase-9 inhibitor results in decreased organism burdens and increased survival of infected animals (52).…”
Section: Bal Fluids Spermidine Acetylspermine Acetylspermidinementioning
confidence: 99%